Analisis Kapasitas Pompa Untuk Penyediaan Air Irigasi Di Kampung Sungai Tengah Kecamatan Sabak Auh Kabupaten Siak - Fuad Riyadhi; Siswanto Siswanto; Yohanna Lilis Handayani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Kampung Sungai Tengah has a productive rice field area of about 450 ha. The extent of rice fields is a potential that can support food availability to meet local and regional needs. The government provides long storage to meet agricultural irrigation water needs, but the quality of crop yields is not maximized and land conversion still occurs. This is caused by difficulties in providing irrigation water due to the absence of pumping development from the government and the lack of understanding of farmers about the function of long storage. In addition, the elevation of the water table during the dry season is lower than the elevation of the rice fields. This research was conducted by using various secondary data and analyzing the feasibility of constructing irrigation pumps in the rice fields of Kampung Sungai Tengah. Based on the data analysis, it was found that the availability of reliable discharge (Q80) of the Siak River using the F.J Mock methods was 147.48 m3/s with the largest irrigation water requirement in April period I of 0.88 m3/s. With a very high level of water availability compared to the irrigation water needs of the area, technically the construction of irrigation pump is feasible.Keywords: Irrigation, Irrigation pump, Feasibility, F.J Mock methods